ANALISIS LAPORAN KEUANGAN SEBAGAI DASAR PENILAIAN PERUSAHAAN WARALABA YANG TERDAFTAR DI BURSA EFEK INDONESIA (STUDI KASUS PADA PT. FAST FOOD INDONESIA, TBK DAN PT. PIONEERINDO GOURMET INTERNASIONAL, TBK PERIODE 2013-2015) - Ratna Kurnia Sari (Monex: Journal of Accounting Research, 2019)
Increased franchise fast food in today's business world led to the emergence of competitive rivalry among entrepreneurs. For that, competition is rampant should be anticipated with careful thought and precise calculation. So that the fast food franchise business that is increasingly growing increasingly in demand in Indonesia. One way to achieve the company's goal is to analyze the financial performance of the company. To measure the performance of companies can be done by comparing the ratios between one company with similar companies. It is very useful to investors in evaluating the condition companies in certain industry groups to determine which one is best and more profitable seen from a comparison of company performance. The main goal of companies engaged in this franchise is to optimize performance in a way to benefit as much as possible. Therefore this study takes the franchise company go public as an object of research, among which PT. Fast Food Indonesia, Tbk and PT. Pioneerindo Gourmet International, Tbk so that it can be seen Which companies are best when seen from its financial performance. In this study, the type of data used is qualitative data which includes company profile and the financial statements for 2013-2015. While the source of the data used is secondary data such as documents of a company's financial statements in 2013-2015 were obtained from the Indonesia Stock Exchange (www.idx.co.id) have been published. Data analysis technique used is the technique of quantitative analysis consists of two company's financial statements including balance sheet and income statement. Where such data will be used as a means of comparison between the financial performance of the company with other similar companies to show the company's financial condition by using financial ratio analysis. Data that will be obtained is the result of the calculation of financial ratios variables. The analysis technique used in this study is the liquidity ratio, solvency, activity ratios, and profitability ratios. Results of research and analysis obtained in terms of liquidity indicates that the current ratio of the two companies has fluctuated, this is due to an increase in liabilities to be paid without any offset by current assets owned. In terms of activity, the two companies are already quite well and effectively manage existing resources in the enterprise such as accounts receivable, inventory and other assets. Of the solvency ratio showed their movement up and down due to the increase in total debt, total assets and total equity capital of the company. And in terms of profitability show a decrease in net income due to the increase in cost of sales to be borne by the company.